PENGARUH PENGEMBANGAN KARIR TERHADAP LOYALITAS KARYAWAN PT.ABC - Olivia Cornelia (Universitas Islam Bandung, 2017)
Human resource is a collection of human labor that exist in a company and become an asset to the company to be managed and developed. One form of employee development is through career development programs. Human resources have an important role for helping the company's performance goals and important for companies to foster a sense of employee loyalty to the company.The objective of this research is to determine how much the impat of career development programs on employee loyalty at PT.ABC .The method used in this research is descriptive and quantitative methods, the study population was all employees at PT.ABC. Samples taken as many as 100 respondents using probability sampling technique by means of random sampling. The analysis includes: validity, reliability, statistical analysis, descriptive, classic assumption test and multiple regression analysis. The results of this study showed that career development programs by PT.ABC are in the very good category (84.43%) and employee loyalty at PT.ABC be in either category (81.18%). Influence Career Development (X) on Employee Loyalty (Y) was 43.7% and the remaining 56.3% is influenced by other factors.